Enhancing Technical Skills Through Hypermedia: An Exploration of Innovative Learning Approach - Mousa, Sawsan; Radif, Mustafa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2024)
The integration of hypermedia in educational contexts has the potential to significantly enhance the development of technical skills, a critical competency in today’s technology-driven world. This paper explores innovative learning approaches facilitated by hypermedia, focusing on its application in technical education. The study begins with a discussion on the general importance of technical skills, followed by a detailed examination of hypermedia as a dynamic and interactive learning tool. Two case studies are presented, demonstrating the successful implementation of hypermedia in educational settings, and the challenges and benefits associated with these approaches are analyzed. The paper concludes with insights into future research directions and emerging trends in hypermedia-enhanced technical education, emphasizing the need for continuous innovation and adaptation in the face of evolving educational technologies.